Mighty to save the sound of worshipping generations. - Hillsong Music Australia (Castle Hill, NSW : Hillsong Music Australia, 2006)
Mighty To Save is the latest live worship album to come out of Hillsong Church! Recorded on March 5th, 2006 and led by Darlene Zschech and the Hillsong team, over 10,000 worshippers at the Sydney Entertainment Centre sang, danced and worshipped their God wholeheartedly and without reserve. These new songs are infused with life, energy and a heartfelt adoration for our Saviour. Our prayer is that you would be inspired to worship in spirit and truth as the message of God's unfailing love and power is declared through these songs.
Disc Two : Special features DVD : Mighty to save: the heart of worship documentary -- A song's journey documentary -- Drum workshop -- Guitar workshop -- Conference and resource information.
Hillsong Music Australia: HMADVD198.
Recorded at the Sydney Entertainment Centre on March 5, 2006.
DVD all regions; NTSC.
Keywords: Music; Songs